APPLICATION OF ERGONOMIC PRINCIPLES IN PRE-CLINICAL TRAINING: DENTAL STUDENTS' PERCEPTIONS - Pazos, Julia Margato [UNESP]; Oliveira, Caroline Anselmi de [UNESP]; Wajngarten, Danielle [UNESP]; Nordi Sasso Garcia, Patricia Petromilli [UNESP]; Arezes, P.; Baptista, J. S.; Melo, R.; Barroso, M.; Branco, J. C.; Carneiro, P.; Colim, A.; Costa, N.; et al. (Portuguese Soc Occupational Safety & Hygiene, 2022)
This study evaluated dental students' perceptions of the application of ergonomic principles during pre-clinical activities. The sample consisted of second-year undergraduate students (n=51). Data was collected using a semi-structured open-ended interview on the challenges to adopting ergonomic posture. The data was analyzed using the discourse of the collective subject (DCS) with QualiQuantiSoft (R). The interviews revealed that most students (54.9%) reported maintaining a distance of 30 to 40 cm between the patient's mouth and the operator's eyes as the most difficult technique to put into practice, particularly when attempting to visualize the operating field (49.0%). The workplace-related factor found to create the greatest risk of developing musculoskeletal disorders was the dental mannequin (31.4%). Most of the students reported that the degree of difficulty of the procedures they were performing negatively influenced their adoption of proper working posture due to the difficulty in visualization (35.3%), to their focus on the work being performed (27.5%), and to their difficulty in accessing the operating field (25.5%). It was concluded that the greatest challenge faced by the students was found to be the ability to maintain an adequate distance between their eyes and the patients' mouths due to the need to visualize the operating field.
Keywords: students; dental; interview; occupational disease